Investigating landfill leachate toxicity in vitro: A review of cell models and endpoints. (January 2019) - Baderna, Diego; Caloni, Francesca; Benfenati, Emilio
Abstract: Landfill leachate is a complex mixture characterized by high toxicity and able to contaminate soils and waters surrounding the dumpsite, especially in developing countries where engineered landfills are still rare. Leachate pollution can severely damage natural ecosystems and harm human health. Traditionally, the hazard assessment of leachate is based on physicochemical characterization but the toxicity is not considered. In the last few decades, different bioassays have been used to assess the toxicity of this complex matrix, including human-related in vitro models. This article reviews the cell bioassays successfully used for the risk assessment of leachate and to evaluate the efficiency of toxicity removal of several processes for detoxification of this wastewater. Articles from 2003 to 2018 are covered, focusing mainly on studies that used human cell lines, highlighting the usefulness and adequacy of in vitro models for assessing the hazard involved with exposure to leachate, particularly as an integrative supporting tool for chemical-based risk assessment. Leachate is generally toxic, mutagenic, genotoxic and estrogenic in vitro, and these effects can be measured in the cells exposed to already low concentrations, confirming the serious hazard of this wastewater for human health. Graphical abstract: Unlabelled Image Highlights: We reviewed 23 papers investigating leachate toxicity in vitro . HepG2, lymphocytes and MCF-7 cells are the most used models. Studies focus mainly on basal toxicity, estrogenicity and genotoxicity. Leachate is toxic, mutagenic, genotoxic and estrogenic already at low concentration. Cell bioassays are successfully used for the risk assessment of leachate.